Decoupled Thermo‐ and pH‐Responsive Hydrogel Microspheres Cross‐Linked by Rotaxane Networks. (26th October 2017) - Kureha, Takuma; Aoki, Daichi; Hiroshige, Seina; Iijima, Keisuke; Aoki, Daisuke; Takata, Toshikazu; Suzuki, Daisuke
Abstract: Rotaxane cross‐linked (RC) microgels that exhibit a decoupled thermo‐ and pH‐responsive volume transition were developed. The pH‐induced changes of the aggregation/disaggregation states of cyclodextrin in the RC networks were used to control the swelling capacity of the entire microgels. Different from conventional thermo‐ and pH‐responsive microgels, which are usually obtained from copolymerizations involving charged monomers, the RC microgels respond to temperature as intended, even in the presence of charged functional molecules such as dyes in the microgel dispersion. The results of this study should lead to new applications, including drug delivery systems that require a retention of their smart functions even in environments that may contain foreign ions, for example, in in vivo experiments.